Judaism and Christianity : new directions for dialogue and understanding - Avery-Peck, Alan J. 1953-; Neusner, Jacob, 1932- (The Brill Reference Library of Judaism, 2009)
This volume treats the interrelationship between Judaism and Christianity from the first centuries and into modern times, paying particular attention to these faiths' social, cultural, and theological interactions. The issues covered range from the formation of Jewish and Christian ideology in the context of Roman paganism to the ways in which Christian culture and theology of the medieval and modern periods form a backdrop to the creation of Jewish identity. While the historical periods and issues discussed are diverse, the result is to suggest the importance of our recognizing the close development of Judaism and Christianity. Written by top scholars in Judaic and Christian studies, these essays reflect on how the two faiths related to and were shaped by each other as they evolved in shared historical and cultural contexts, even as each maintained its own distinctive ideologies and beliefs.